An Electronic Clinical Decision-Making Tool for Patients with Suspected Colorectal Cancer—Preliminary Evaluation in Patients Presenting with Rectal Bleeding. Issue 5 (22nd May 2019) - Forbes, Nauzer; Cooray, Mohan; Hackett, Michael; Shah, Nishwa; Yuan, Yuhong; Antiperovitch, Pavel; Corner, Tracey; Chan, David; Mills, Michael; Armstrong, David; Xenodemetropoulos, Ted
Abstract: Background and Objectives: The CarePath-CRC electronic clinical decision-making application was designed to assist physicians with evaluation of patients with suspected colorectal cancer (CRC). The physician completes an interactive checklist of evidence-based clinical parameters, and a recommended referral urgency is generated based on the post-test probability of CRC. This study aimed toward validation of the tool in symptomatic patients presenting with rectal bleeding. Methods: The medical records of a sample of patients with histologically confirmed CRC from 2010 to 2014 were reviewed. The CarePath-CRC tool was applied retrospectively to all patients who initially presented with rectal bleeding, to determine its sensitivity for detecting CRC in this population. A generated recommendation of 'immediate referral' (referral ≤24 hours, expected endoscopy ≤2 weeks) or 'urgent referral' (expected consultation and endoscopy ≤4 and ≤8 weeks) was considered a positive test result. An a priori sensitivity of 90% was deemed adequate, based on test characteristics of the tool's individual clinical criteria. Results: The tool was applied to 281 patients. A total of 69 (24.6%) and 211 (75.1%) patients met criteria for immediate and urgent referral, respectively. The remaining patient (0.4%) met criteria for 'possible priority referral', while none met criteria for 'no specific action recommended'. This resulted in a calculated sensitivity of 99.6% (95% confidence interval 98.0 to 99.9%). Conclusions: The CarePath-CRC tool is sensitive in the prediction of CRC in patients presenting with rectal bleeding. A prospective cohort study is being designed to allow for acquisition of comprehensive test performance characteristics and full validation of the instrument.